1986
DOI: 10.1111/j.1745-4565.1986.tb00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone in Native Cereal Beer Brewed in Jos Metropolis of Nigeria

Abstract: Native cereal beer, pito, brewed in Jos metropolis during the 1984 late planting season was screened for zearalenone content. Zearalenone was detected in pito from 28 of the 46 breweries in 13 of the 14 districts sampled, with mean concentration of 81.75 ± 50.16 μg/liter and range 12.50–200.00 μg/liter. Aflatoxin B1 was detected in pooled extracts. There were other chloroform‐soluble isolates but their identities could not be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Investigation (Okoye et al, 2002) has revealed that aquatic organism in River Niger has nickel concentration of mean value 1.23 ppm higher than the value obtained from Aba river. High concentration of Ni in fish poses health hazard to human beings who eat fish.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Investigation (Okoye et al, 2002) has revealed that aquatic organism in River Niger has nickel concentration of mean value 1.23 ppm higher than the value obtained from Aba river. High concentration of Ni in fish poses health hazard to human beings who eat fish.…”
Section: Discussionmentioning
confidence: 76%
“…Nwaedozie (1998) working on Kaduna river reported Zn concentration of mean value 6.60 ppm in fresh catfish. Okoye et al (2002) working on the River Niger reported Zn concentration of mean value 2.32 ppm in aquatic organisms. The Zn level obtained from River Niger is lower than the values obtained from Aba and Kaduna rivers, this may be due to fewer industries that discharge waste into the River Niger.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Some traditional 'opaque' African beers, as a result of fungal grain infection, have been reported to contain different amounts of aflatoxins. These aflatoxins appear to have a more harmful effect on animals than on humans (Okoye 1986). …”
Section: Steeping Of Sorghum Grainsmentioning
confidence: 98%